2016
DOI: 10.1007/s00066-016-1040-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel injection reduces rectal toxicity after radiotherapy for localized prostate cancer

Abstract: Spacer injection is associated with a significant benefit for patients after prostate cancer RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…A few studies have examined long‐term toxicities in patients treated with IMRT for prostate cancer with and without SpaceOAR. Our report therefore adds to the available information, which is summarised in Table . After a minimum follow‐up of 2 years, Whalley et al reported lower rates of late grade 1 gastrointestinal toxicity in their SpaceOAR group (16.6%) compared to patients treated without a SpaceOAR (41.8%).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A few studies have examined long‐term toxicities in patients treated with IMRT for prostate cancer with and without SpaceOAR. Our report therefore adds to the available information, which is summarised in Table . After a minimum follow‐up of 2 years, Whalley et al reported lower rates of late grade 1 gastrointestinal toxicity in their SpaceOAR group (16.6%) compared to patients treated without a SpaceOAR (41.8%).…”
Section: Discussionmentioning
confidence: 79%
“…Our report therefore adds to the available information, which is summarised in Table 3. [13][14][15][16] After a minimum follow-up of 2 years, Whalley et al 15 reported lower rates of late grade 1 gastrointestinal toxicity in their SpaceOAR group (16.6%) compared to patients treated without a SpaceOAR (41.8%). A single-blind, randomised trial of 222 eligible men from 20 participating institutions 14 reported benefits of the SpaceOAR gel at 15 months for bowel toxicity; quality of life (QOL) was maintained or had increased at 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported similar results to our present study, with no significant adverse events related to HS injection and no differences in the rates of acute rectal toxicity between the HS and control groups. Another study by Pinkawa et al , reported on 167 consecutive patients treated either with HS ( n = 110) or without HS ( n = 66), whilst undergoing prostate RT up to a maximum dose of 80 Gy. These authors also reported similar findings to our present study, in that the HS injection was found to result in favourable rectal dosimetry with minimal acute rectal toxicity during and shortly after RT.…”
Section: Discussionmentioning
confidence: 99%
“…Most experience with hydrogel injection has been in the region between the prostate and rectum for men receiving dose-escalated prostate RT (25-28). Recently reported results of a phase III study of dose-escalated IMRT for prostate cancer in 222 men randomized 2:1, with and without spacer placement, respectively, demonstrated a reduced rectal dose and toxicity and improved quality of life (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, hydrogel injection for spacing organs at risk (OARs) from the radiation target to increase the deliverable dose or improve the safety of RT has been evaluated most extensively in the treatment of prostate cancer (25-28), with some experience in gynecologic cancers as well (29). Hydrogel spacer injection between the rectum and prostate and seminal vesicles has resulted in a reduced rectal dose and toxicity and improved quality of life (25).…”
Section: Introductionmentioning
confidence: 99%